Pengaruh Work From Home terhadap Produktivitas Kerja Karyawan pada Issue Covid 19 - Dinar Maudina Lestari; Sri Suwarsi (Bandung Conference Series: Business and Management, 2022)
Abstract. The impact of the COVID-19 pandemic on the world of employment in Indonesia is seen from the side of workers, entrepreneurs and independent businesses. PT. Bismacindo Perkasa is a company engaged in the field of IT. The application of working from home or Work From Home does not have much impact on its employees. Since the spread of the Covid 19 virus and the government's enactment of a lockdown, all private and public companies must implement Work From Home . Therefore, this research is to analyze whether there is an effect of Work From Home on Employee Work Productivity in the Covid 19 Issue which aims to find out how it is implemented, find out work productivity and find out the impact of Work From Home using the SPSS method. This research was basically developed with a quantitative and verification approach. The sample in this study amounted to 37 respondents, who used employees at PT. Bismacindo Perkasa, West Jakarta. This study uses primary data collected through questionnaires. Data were analyzed using simple regression analysis. The results of this study are to show that Work From Home has an effect on Employee Work Productivity in the Covid 19 Issue. Dampak Pandemi Covid 19 terhadap dunia ketenagakerjaan di Indonesia dilihat dari sisi pekerja, pengusaha dan usaha mandiri. PT.Bismacindo Perkasa merupakan perusahaan yang bergerak di bidang penyedia IT. Penerapan bekerja dari rumah atau Work From Home tidak terlalu berdampak bagi karyawannya. Semenjak maraknya virus Covid 19 dan diberlakukannya lockdown oleh pemerintah maka seluruh perusahaan swasta maupun negeri harus memberlakukan Work From Home . Maka dari itu penelitian ini untuk menganalisis apakah terdapat Pengaruh Work From Home Terhadap Produktivitas Kerja Karyawan Pada Issue Covid 19 yang bertujuan untuk mengetahui bagaimana pelaksanaan, mengetahui produktivitas kerja dan mengetahui dampak dari Work From Home dengan menggunakan metode SPSS. Penelitian ini pada dasarnya dikembangkan dengan pendekatan kuantitatif dan verikatif. Adapun sampel dalam penelitian ini berjumlah 37 responden, yang menggunakan karyawan di PT.Bismacindo Perkasa Jakarta Barat. Penelitian ini menggunakan data primer yang dikumpulkan melalui kuisioner. Data dianalisis menggunakan analisis regresi sederhana. Hasil penelitian ini untuk menunjukan bahwa Work From Home berpengaruh Terhadap Produktivitas Kerja Karyawan Dalam Issue Covid 19.